Work flexibility dan nonfinancial compensation sebagai prediktor employee retention generasi milenial di DKI Jakarta - Anggun Rahmawati; Wendra Wendra (Jurnal Manajemen Maranatha, 2025)
Data shows that millennial generation workers in Indonesia are ranked second in the Asia Pacific region who plan to resign from their jobs in the future, so organizations need to understand the variables that influence the retention of these millennial employees. This research aims to identify the influence of work flexibility and non-financial compensation on employee retention of millennial generation employees in DKI Jakarta. Data collection was carried out at convenience for 145 respondents. The analytical method used in this research was descriptive statistic and multilinear regression using JASP software. The results of this research show that there is a positive and significant influence of work flexibility and non-financial compensation on employee retention of the millennial generation in DKI Jakarta. Thus, organizations should provide opportunities for employees to arrange the time and location for completing work if they are unable to attend the office, as well as providing an allowance to work outside the office every week. Apart from that, it is also necessary to consider providing non-financial compensation to employees in the form of social support, recognition for achievements, providing work challenges, and giving trust as an effort to retain their millennial generation employees.